2005
DOI: 10.1039/b510348g
|View full text |Cite
|
Sign up to set email alerts
|

Novel fluorogenic calix[4]arene-bis(crown-6-ether) for selective recognition of thallium(i)

Abstract: A new fluorogenic, dansyl group-containing derivative of 1,3-alternate calix[4]arene-bis(crown-6-ether) provides optical recognition of Tl+ with selectivity over many other metal cations, including Na+, K+, Ca2+, Ag+, Hg2+ and Pb2+, and embodies the first example of a calixarene-based fluorescent Tl+-chemosensor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…These molecules have been incorporated into various systems to detect traces of thallium in water, even in the presence of other cationic species. [31][32][33][34][35] More recently, another class of macrocyclic derivatives showing high affinity for Tl(I) in aqueous solution has emerged. [36][37][38] These compounds are interesting because the number of host molecules that can bind Tl(I) in aqueous phase are rather limited and most of the studies reported in the literature have concerned macrocyclic compounds dissolved in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules have been incorporated into various systems to detect traces of thallium in water, even in the presence of other cationic species. [31][32][33][34][35] More recently, another class of macrocyclic derivatives showing high affinity for Tl(I) in aqueous solution has emerged. [36][37][38] These compounds are interesting because the number of host molecules that can bind Tl(I) in aqueous phase are rather limited and most of the studies reported in the literature have concerned macrocyclic compounds dissolved in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Two fluoroionophores of this type have been reported, a 1,3-alternate calix [4]arene-bis(crown-6-ether) 8 (Figure 1) (48) and a conformationally mobile calix [4]arene 9 (49). Both of these mono(N-dansylcarboxamides) demonstrated high selectivity towards Tl þ and both of them behaved as multi-purpose chemosensors that, in contrasting modes, allowed for the detection of two different heavy metal ions.…”
Section: Gg Talanova and Vs Talanov 844mentioning
confidence: 99%
“…Known metal-sensing dansyl-containing fluorogenic calixarenes (as well as thiacalixarenes) vary in the fashion of the fluorophore attachment to the receptor moiety as HN-dansyl (37,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) and O-dansyl ligands (36,(55)(56)(57) (for the structural formulae, see Figures 1-4). In the former type, the anchor NH-group usually is a part of carbamoyl or aminoalkyl linker, or it may be bound directly to the aromatic ring of the calixarene; while in the latter type, the dansyl moiety is a substituent on the calixarene lower-rim phenolic oxygen.…”
Section: General Characteristics Of Dansyl-containing Calixarene-basementioning
confidence: 99%
“…[20][21][22] In some instances, dansyl fluorophores were incorporated into these structures for possible investigation of the complexation properties of such calix [4]arenes by solution fluorescence spectroscopy.…”
Section: Introductionmentioning
confidence: 99%